Anti-tumour efficacy of human mesenchymal stem cell expressing trail on lung cancer cell lines-derived cancer stem cell - Shaik M Fakiruddin, Shaik Ahmad Kamal (2021)
Disturbing increase in the global lung cancer cases and cancer-related mortality justifies the needs for therapies that are effective and tumour selective. TNF-related apoptosis inducing ligand (TRAIL) has been shown to be a promising therapeutic agent against several tumours, including cancer stem cells (CSCs). However, due to its short half-life and poor bioavailability, TRAIL needs a delivery system to be effective. Mesenchymal stem cells (MSCs) have recently emerged as an effective anti-tumour cytotherapy, able to deliver TRAIL in pre-clinical tumour models. However, investigations on its efficacy to target CSC in non-small cell lung cancer (NSCLC), is lacking. Thus, this study is designed to investigate the efficacy of MSCs expressing TRAIL (MSC-TRAIL) either as a single agent or in combination with first line chemotherapies to destroy CSC isolated from NSCLC cell lines (A549, H2170 and H460). The human MSCs were successfully transduced with TRAIL-encoding lentivirus which resulted in MSC-TRAIL. The generated MSC-TRAIL expressed elevated levels of TRAIL protein and maintained mesodermal lineages differentiation and MSCs surface markers. The CD133+ CSC was isolated from the NSCLC cell lines and verification assays were subsequently performed. It was observed that the sorted CD133+ population strongly exhibited the characteristics of CSCs based on their bigger sphere size detected in an anchorage independent culture, significantly higher number of colonies, and expression of aldehyde dehydrogenase (ALDH), when compared to the non-CSC’s control (CD133-). Furthermore, flow cytometry analyses have also revealed that the expression of DR5 TRAIL receptor was high in the CD133+ CSC population in both H2170 and H460 compared to A549. It was observed that the co-culture of MSC-TRAIL and the CD133+ population from both H460 and H2170 induced a significant inhibition to the CSCs. Furthermore, inhibitions to both the unsorted and CD133- cells were also found, indicating that the MSC-TRAIL was effective in destroying the tumour. The MSC-TRAIL was noticed to induce apoptosis and cell death to both H460 and H2170-derived CD133+ CSCs, indicated by the positive annexin V and sytox-green stained cells. Through investigation of the mitochondrial membrane potential, it was also found that MSC-TRAIL was able to induce intrinsic apoptosis to the CSCs. Sensitisation of the NSCLC cell lines using first line chemotherapies prior to exposure to MSC-TRAIL was able to induce a chemo-sensitising effect to the CSCs. Further analyses using gene expression profiling have uncovered candidate genes including NFKB1, BAG3, MCL1, GADD45A, and HRK in CD133+ CSCs, which, if targeted, might increase the sensitivity of NSCLC to MSC-TRAIL-mediated inhibition. As such, these findings add credibility to the use of MSC-TRAIL as anti-tumour cytotherapy and help to uncover a unique therapeutic potential of MSC-TRAIL in the treatment of NSCLC by targeting the CD133+ CSCs.